1992
DOI: 10.1007/bf00348123
|View full text |Cite
|
Sign up to set email alerts
|

Small angle neutron scattering from oxygen precipitates in silicon

Abstract: Abstract. The formation of silicon oxide precipitates from Czochralski grown silicon depends on the time and temperature of the heat treatment as well as on the initial content of interstitially dissolved oxygen. Samples containing between 5 x 1017 Oi/cm 3 and 13 x 1017 Oi/cm 3 have been heated at 750°C for 96 h. SiO2 precipitates of various shape and size have been obtained and investigated by means of small angle neutron scattering (SANS) in the Q-range 0.05 A-~ < Q < 0.2 A-1. The obtained SANS patterns reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…where Oi denotes an interstitial oxygen atom, V a vacancy, Si I a silicon self-interstitial and 2 SiO an oxygen precipitate. Therefore, it is evident that the point defects are actively involved in oxygen precipitation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where Oi denotes an interstitial oxygen atom, V a vacancy, Si I a silicon self-interstitial and 2 SiO an oxygen precipitate. Therefore, it is evident that the point defects are actively involved in oxygen precipitation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been proved that oxygen precipitation in silicon can be affected by initial oxygen contents [2], other impurities [3][4][5], annealing temperature [6], thermal history [7], point defects [8][9][10], and annealing atmosphere [9][10][11]. Hu has reported that the oxidizing atmosphere strongly retard oxygen precipitation in comparison with the inert gas atmosphere and attibuted this phenomenon to the excess silicon self-interstitials generated during thermal oxidation [9].…”
Section: Introductionmentioning
confidence: 99%
“…The supersaturated oxygen in CZ silicon wafers can form oxygen precipitates, which act as effective gettering sites for heavy metals during semiconductor device manufacturing processes. 1,2) In past decades, oxygen precipitation in silicon can been influenced by oxygen content, 3,4) other impurities, [5][6][7] point defects 8,9) and thermal circles 10) has been investigated intensively. Recently, due to nitrogen's special properties in silicon, its effect on oxygen precipitation in CZ silicon has been receiving attention, along with the increasing diameter of CZ crystals.…”
Section: Introductionmentioning
confidence: 99%
“…In Czochralski (CZ) silicon, oxygen precipitates are used as effective gettering sites for heavy metals during device processes [1,2]. It is well known that oxygen precipitation in CZ silicon can be influenced by oxygen content [3], impurities [4,5], annealing temperature [6], and point defects [7][8][9][10]. Voronkov et al [10] have suggested that the vacancies incorporated in CZ silicon during crystal growth hardly affect oxygen precipitation at temperatures above the void onset temperature (around 1070 °C), but they could interact with oxygen atoms to form O 2 V species at lower temperature, which will enhance oxygen precipitation following the void formation.…”
Section: Introductionmentioning
confidence: 99%